Obstacles to complying with health protocols in coronavirus disease 2019 patient care among emergency medical staff of Zanjan province in 2022 - Ghasim Sadeghi; Seyede Fatemeh Gheiasi; Soheila Rabie Siahkali; Kamyar Mansori (Zanjan University of Medical Sciences and Health Services, 2024)
Background: As a capable arm of the healthcare system, emergency medical staff play a major role in the evolution and growth of healthcare services and the improvement and promotion of society's health. One of the problems in providing ideal care during the coronavirus disease 2019 (COVID-19) pandemic across the world, including Iran, was complying with health protocols. Objectives: The current study aimed to investigate the obstacles to complying with health protocols in COVID-19 patient care from the emergency medical staff's perspectives. Methods: This cross-sectional study was conducted on 197 emergency medical staff in Zanjan province in 2022. Sampling was done by cluster random method. Data were collected using a researcher-made questionnaire in 4 parts, including demographic characteristics, organizational obstacles, social obstacles, and individual obstacles. Data were analyzed using descriptive and inferential statistics in SPSS 16 software. Results: All participants were male, with a mean (SD) age of 33.15 (5.09) years. The mean (SD) score of the obstacles to complying with health protocols questionnaire from the participants' perspectives for organizational, individual, and social factors were 3.92 (0.49), 3.47 (1.06), and 3.32 (1.12), respectively. According to the participants' perspectives, shortage of equipment 4.53 (0.79), long-term use of personal protective equipment (PPE) 4.46 (0.66), and insufficient specialized training for COVID-19 4.18 (1.11) were the most important obstacles in complying with the COVID-19 health protocols. Conclusion: It is suggested that managers and policymakers pay attention to the obstacles identified in the present study and take these obstacles into account in the emergence of newfound future diseases.